Chemical characterization and cytotoxic effect of three edible fungi (Morchella) against breast cancer cells: A therapeutic approach (Kuwait Journal of Science)
Current breast cancer therapeutics are associated with short-term efficacy, increased drug resistance, and severe adverse reactions, thus demanding the development of new therapeutic approaches. This present study aimed to explore the cytotoxic activity of Morchella extracts in the context of the MCF-7 cell line (breast cancer) and ultra-performance liquid chromatography mass spectroscopy (UPLC-MS) analysis. The cytotoxic activity of the Morchella conica, Morchella delicosa, and Morchella escuelnta extracts was examined against the breast cancer cell line (MCF-7), using a 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay (MTT assay). The Morchella extracts were screened for the presence of compounds using ultra-performance liquid chromatography mass spectroscopy (UPLC-MS/MS) based analysis. All the Morchella extracts actively restricted the viability and proliferation of breast cancer cells in a dose-dependent manner, with half maximal inhibitory concentration (IC50) values ranging from 0.017 to 0.68 mg/ml. The main compounds identified in Morchella include alkaloid, sterol, flavonoid, terpenoid, fatty acid, peptide, glutamic acid, amino acid, coumarin, and cyclopyrrolone. In conclusion, Morchella extracts exhibited cytotoxic effects against breast cancer cell lines and decreased the viability of MCF-7 cell line. The Morchella compounds might be the main components contributing to the inhibition of breast cancer cells. The findings of this research offer an innovative framework for advanced investigations for the development of cancer therapeutics from this fungus. © 2024 The Authors